ANALISIS PENGARUH RETURN ON ASSET, CAPITAL ADEQUACY RATIO, LOAN TO DEPOSIT RATIO TERHADAP TINGKAT KREDIT MACET PADA PERUSAHAAN PERBANKAN BUMN TAHUN 2017-2019 - Thesya Yuzevin; yacobo p sijabat (Universitas Muhammadiyah Gresik, 2020)
Banks are briefly defined as business entities that collect funds from the public and channel them back to the public in the form of credit or other forms, which are one of the influential sectors in a country's economy. Channeling funds to the public or also called credit (leasing) aims to help improve the lives of many people. The existence of this loan often faces problems, namely non-performing loans (NPLs) where there are credit risks faced by the Bank due to the inability of the customer or debtor to return the amount of loans received from the Bank along with interest within a predetermined period of time. This study aims to determine the effect of Return On Assets (ROA), Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR) on the level of non-performing loans (NPLs) in SOE banking companies in 2017-2019. The research method used is descriptive quantitative by using combined panel data from cross sections and time series using SOE Bank financial report data for the 2017-2019 period. The results of this study indicate the influence of ROA on NPL, while CAR and LDR do not have a significant effect that indicates good company performance. Keywords: Bank, NPL, ROA, CAR, LDR